Analisis Model Penerimaan Teknologi Pada Wajib Pajak Dalam Menggunakan Sistem E-Billing Di Kantor Pelayanan Pajak Pratama Merauke - Mohamad Ilham (Jurnal Mantik Penusa, 2017)
E-billing system is a new challenge for taxpayers in the fulfillment of tax obligations in accordance with Director General tax(DGT) Regulation No. PER-26 / PJ / 2014 on the Electronic Tax Payment System.In fulfillment of tax obligations (paying taxes) using a new technology that will provide behavioral responses and perceptions vary by each taxpayer that ultimately can be considered for the development of future such systems.This research analyzes the behavior of corporate taxpayers on KPP PratamaMerauke as the e-billing system using the technology acceptance model (TAM).The research aim to investigate the factors (variables) that influence the behavior of taxpayers acceptance of the application of e-billing system at the Tax Office (KPP) PratamaMerauke.Population and sample in this research is a registered taxpayer in KPP PratamaMerauke, number of samples in this research of 100 taxpayers.The sampling technique used is incidental sampling.Sampling is incidental sampling technique based on chance, as taxpayers who by chance / incidental been to KPP PratamaMerauke on during the period January to February 2017.Analysis of the data in this study using multiple linear regression with SPSS 20. The results research indicate that the perception of usefulness and perceived ease of significant positive effect on the attitude; perceived usefulness, attitude, and experience significant positive effect on behavioral intention to use; The experience had a significant positive effect on the perception of usefulness.